Estimation of Biomass, Carbon Stocks, O2 Production and Enviromental Services Value of CO2 Sequestration of Mangrove Forest in Kurau Sub-District, Tanah Laut Regency - Abdi Fithria; Syam’ani D. Ali; Udiansyah Udiansyah; Muhammad Ruslan; Arfa Agustina Rezekiah; Hilman Fahmi; Achmad Arya Diva; Firman Pramudya Rahmat Wahyudi; Pani Akbar; Yasinta Nur Shiba (Jurnal Ilmu Lingkungan, 2025)
Indonesia possesses the world’s largest mangrove forest area, which plays a vital role in global carbon regulation and coastal ecosystem services. However, these ecosystems are under increasing threat from anthropogenic pressures such as aquaculture expansion (especially shrimp farming), agricultural land conversion, and urban infrastructure development. These activities not only reduce forest cover but also compromise the ecological functions of mangroves, particularly their role as significant carbon sinks and oxygen producers. Given that mangroves have the highest carbon storage capacity per hectare compared to other forest types, their conservation is imperative in mitigating climate change. This study aims to assess the ecological and economic functions of mangrove forests in Kurau Sub-district, Tanah Laut Regency, South Kalimantan. Specifically, it quantifies aboveground biomass, carbon stocks, oxygen output, and the economic value of CO₂ sequestration. Data were collected through stratified random sampling based on vegetation density classes obtained from NDVI imagery, categorized into sparse, moderate, and dense classes. Field measurements focused on vegetation components from saplings to mature trees. Biomass was calculated using species-specific allometric equations, carbon stock was estimated by applying standard conversion factors, and oxygen production was derived using stoichiometric ratios. Economic valuation was conducted using a market-based approach, referencing global carbon pricing standards. The findings reveal that dense vegetation areas provide the greatest ecological benefit, with biomass of 54.72 tons/ha, carbon stock of 25.72 tons/ha, and oxygen production of 68.66 tons/ha. These ecological values translate into an estimated economic benefit of IDR 1.57 billion per year, indicating potential for integrating mangrove conservation with community-based development programs.